"{y}'\\left(x\\right)=\\lim\\limits_{h\\to 0}\\frac{y\\left(x+h\\right)-y\\left(x\\right)}{h}"
a)
"{y}'\\left(x\\right)=\\lim\\limits_{h\\to 0}\\frac{\\frac{1}{\\sqrt {x+h} } -\\frac{1}{\\sqrt x}}{h}"
Move the h into the numerator functions' denominators
"=\\lim\\limits_{h\\to 0}\\frac{1}{h\\sqrt {x+h} } -\\frac{1}{h\\sqrt x}"
Get common denominators by cross-multiplying.
"=\\lim\\limits_{h\\to 0}\\frac{1}{h\\sqrt {x+h} } \\frac{\\sqrt {x}}{\\sqrt {x} }-\\frac{1}{h\\sqrt x}\\frac{\\sqrt {x+h}}{\\sqrt {x+h} }"
"=\\lim\\limits_{h\\to 0}\\frac{\\sqrt {x}}{h\\sqrt {x+h}\\sqrt {x} }-\\frac{\\sqrt {x+h}}{h\\sqrt {x+h}\\sqrt x}"
Multiply by the complex conjugate of the resultant numerator as a fraction equal to 1
"=\\lim\\limits_{h\\to 0}\\frac{\\sqrt {x}-\\sqrt {x+h}} {h\\sqrt {x(x+h)} } * \\frac{\\sqrt {x}+\\sqrt {x+h}} {\\sqrt {x}+\\sqrt {x+h}}"
"=\\lim\\limits_{h\\to 0}\\frac{{x}- (x+h)} {h\\sqrt {x(x+h)}(\\sqrt {x}+\\sqrt {x+h}) }"
Thus, you get a cancellation of x in the numerator and h is by itself.
"=\\lim\\limits_{h\\to 0}\\frac{-h} {h\\sqrt {x(x+h)}(\\sqrt {x}+\\sqrt {x+h}) } =\\\\"
"=\\lim\\limits_{h\\to 0}\\frac{-1} {\\sqrt {x(x+h)}(\\sqrt {x}+\\sqrt {x+h}) } =\\frac{-1} {2x\\sqrt {x} }=\\frac{-1} {2x^{3\/2 }}" .
b)
"{y}'\\left(x\\right)=\\lim\\limits_{h\\to 0}\\frac{\\sqrt {x+h+1} -\\sqrt {x+1} }{h}"
"{y}'\\left(x\\right)=\\lim\\limits_{h\\to 0}\\frac{\\sqrt {x+h+1} -\\sqrt {x+1} }{h}=\\\\\n\n =\\lim\\limits_{h\\to 0}\\frac{(\\sqrt {x+h+1} -\\sqrt {x+1}) (\\sqrt {x+h+1} +\\sqrt {x+1}) }{h (\\sqrt {x+h+1} +\\sqrt {x+1})}=\\\\\n\n=\\lim\\limits_{h\\to 0}=\\frac{( {x+h+1} - x-1) }{h (\\sqrt {x+h+1} +\\sqrt {x+1})} = \\\\ =\\lim\\limits_{h\\to 0}\\frac{ {h} }{h (\\sqrt {x+h+1} +\\sqrt {x+1})}=\\\\=\\lim\\limits_{h\\to 0}\\frac{ {1} }{ (\\sqrt {x+h+1} +\\sqrt {x+1})}=\\\\\n=\\frac{ {1} }{ \\sqrt {x+1} +\\sqrt {x+1}}=\\frac{ {1} }{ 2\\sqrt {x+1}}."
--------------------------------------------------------------------------------------------------------------
2.
a)
"y= \\exp(1\/2x) +\\cos x \\sin x"
Find the first derivative
"y'= ( e^{1\/2x} +\\cos x \\sin x)'= \\\\ = ( e^{1\/2x}) + \\frac{1}{2} \\sin 2x)'=\\\\ =\n \\frac{1}{2} e^{1\/2x} + \\frac{1}{2} 2\\cos 2x= \\\\\n= \\frac{1}{2} e^{1\/2x} +\\cos 2x"
"y'= \\frac{1}{2} e^{1\/2x} +\\cos 2x" .
b)
"y= \\sqrt{ e^{ax}} \\sin x"
"y'= (y= \\sqrt{ e^{ax}} \\sin x)'= \\\\ =\n (\\sqrt{ e^{ax}})' \\sin x+ \\sqrt{ e^{ax}}( \\sin x)'=\\\\\n= \\frac{a e^{ax}\\sin x} {2\\sqrt{ e^{ax}}}+ \\sqrt{ e^{ax}}( \\cos x)= \\frac{e^{ax}(a \\sin x+ 2\\cos x)} {2\\sqrt{ e^{ax}}}".
"y'= \\frac{e^{ax}(a \\sin x+ 2\\cos x)} {2\\sqrt{ e^{ax}}}" .
3.
a)
"\\frac{dy} {dx}= \\left(\\frac{\\sin x \\cos x}{\\cos 2x} \\right)'= \\left(\\frac{1}{2}\\frac{\\sin 2x }{\\cos 2x} \\right)'= \\left( \\frac{1}{2}\\tan 2x \\right)'= \n\\\\ \\frac{1}{2}\\frac{1}{\\cos^2 2x} *2=\\frac{1}{\\cos^2 2x}"
"\\frac{dy} {dx}= \\frac{1}{\\cos^2 2x}" .
b)
"\\frac{dy} {dx}= \\left(\\frac{ {\\sqrt {x+1}} }{ \\sqrt {x-1}} \\right)'=\\left(\\frac{ {(\\sqrt {x+1})'\\sqrt {x-1}- (\\sqrt {x-1})'\\sqrt {x+1}} }{ (\\sqrt {x-1})^2} \\right)=\\\\ \n=\\left(\\frac{ {\\frac{ {1} }{2 \\sqrt {x+1}}\\sqrt {x-1}- \\frac{ {1} }{2 \\sqrt {x-1}}\\sqrt {x+1}} }{ {x-1}} \\right)=\\frac{ {1} }{ {x-1}}\\frac{ {-2} }{ {2 \\sqrt {x+1} \\sqrt {x-1}}}= \\\\ =\\frac{ {-1} }{ { \\sqrt {x+1} ({x-1})^\\frac{3}{2}}}" =
"\\frac{dy} {dx}= =\\frac{ {-1} }{ { \\sqrt {x+1} ({x-1})^\\frac{3}{2}}}" .
Comments
Leave a comment